Glocal Language Policy: An Approximation to Deconstruct Internationalization in A Colombian University - Torres, Cubides-; Sarracino, Toledo-; Rodriguez, Montaño- (Journal of Posthumanism, 2026)
The objective of this article is to analyze how teaching practices informed by a glocalized approach and an internationalization framework can support the design of a glocalized language policy in a public university located in the central region of Colombia. This qualitative case study was conducted under an interpretative paradigm using thematic analysis of in-depth interviews with foreign language teachers. The analysis was conducted through the theoretical perspectives of Chen’s (2023) Globalization–Localization Interaction Dynamics Model (GLIDM) and Patel’s (2017) Glocal Engagement Framework (GEF). Findings reveal that teaching practices are articulated through global, glocal, and local dimensions, which not only reproduce global hegemonies of English teaching, but also create spaces of intercultural engagement. Thus, teaching practices provide tangible evidence for designing a glocalized language policy in Colombian context, which implies safeguarding cultural and language diversity while engaging in global dialogues, with initial implications for curriculum, community, and materials policies.